Identifying the Antecedents of Employee Perceptions of Human Resource Practices Using Signaling Theory - Aryan Gholipour; Mohammad Abooyee Ardakan; Neda Mohammad Esmaeili; Atiyeh Rasouli (مدیریت دولتی)
Objective In the relational models between human resource management and organizational performance, employees' perceptions of human resource practices play a crucial role. For an organization to achieve its desired outcomes, it is essential that employees understand and interpret HR practices as they are intended by the organization. One of the key goals of human resource management is to foster positive employee attitudes, behaviors, and performance. In other words, organizations design and implement HR systems and processes that aim to achieve these goals and desired outcomes. According to relational models between HR management and performance, such as the process model of strategic human resource management (Wright and Nishii, 2007, 2013), employees' perceptions of HR practices are more closely related to attitudinal, behavioral, and performance outcomes than the actual HR practices themselves. Therefore, shaping and aligning employees' perceptions with the intended goals of HR management can significantly contribute to achieving desired results at various levels—individual, team, and organizational. In light of this importance, the present study was conducted to address two key research questions: How can HR messaging be optimized to reduce the gap between the messages sent by HR professionals and the messages received by employees? Additionally, what specific factors influence and shape employees' perceptions of HR practices? The main goal of this research was to identify the drivers, antecedents, or elements that significantly influence the formation of employee perceptions of HR practices Methods To conduct the present research, a systematic literature review (SLR) method was employed. Using keywords related to employee perceptions of human resources, approximately 1,000 articles from 2004 to 2022 were identified and reviewed. Ultimately, 134 articles were analyzed to extract the antecedents of employees' perceptions of HR practices, according to the dimensions of signaling theory. The analysis sought to understand how these antecedents interact with and influence employees’ perceptions across different contexts. Results The research findings indicate that employee perceptions of HR practices are influenced by the characteristics of HR management signalers, the nature and clarity of HR management signals, environmental or contextual conditions, and the characteristics of the receivers of HR signals. Additionally, the study highlights that seeking and obtaining regular feedback from employees about HR practices can help refine and improve the effectiveness of HR signals, the role of HR signalers, and contextual factors under the organization's control, thereby better aligning employee perceptions with the strategic objectives of HR practices. Conclusion To effectively create and evaluate HR practices, HR managers and researchers must pay close attention to employee perceptions and the factors that shape them. Considering this, HR communication and its various dimensions can play a significant and effective role in shaping and improving employee perceptions. By focusing on the antecedents of employees' perceptions of HR management, managers can reduce the gap between the three levels of HR management: intended HR management, implemented or actual HR management, and perceived HR management. Moreover, a deep understanding of these perceptions can empower organizations to develop more strategic and impactful HR practices that resonate well with employees, leading to improved organizational performance and employee satisfaction.